High Cholesterol Deteriorates Bone Health: New Insights into Molecular Mechanisms - Mandal, Chandi C. (Frontiers in Endocrinology, 2015)
Many epidemiological studies show a positive connection between cardiovascular diseases and risk of osteoporosis, suggesting a role of hyperlipidemia and/or hypercholesterolemia in regulating osteoporosis. The majority of the studies indicated a correlation between high cholesterol and/or high LDL-cholesterol level with low bone mineral density, a strong predictor of osteoporosis. Similarly, bone metastasis is a serious complication of cancer for patients. Several epidemiological and basic studies have established that high cholesterol is associated with increased cancer risk. Moreover, osteoporotic bone environment predisposes the cancer cells for metastatic growth in the bone microenvironment. This review focuses on how cholesterol and cholesterol-lowering drugs (statins) regulate the functions of bone residential osteoblast and osteoclast cells to augment or to prevent bone deterioration. Moreover, this study provides an insight into molecular mechanisms of cholesterol-mediated bone deterioration. It also proposes a potential mechanism by which cellular cholesterol boosts cancer-induced bone metastasis.